Sonographic Wrist Measurements and Detection of Anatomical Features in Carpal Tunnel Syndrome - Esther Vögelin; Thomas Mészàros; Franziska Schöni; Mihai A. Constantinescu (The Scientific World Journal)
Introduction. This study compares anatomical findings at wrist level in patients with known carpal tunnel syndrome (CTS) and controls by ultrasonography (US). Material and Methods. Wrist-US investigations of 28 consecutive patients with 38 diagnosed, idiopathic CTS were compared to 49 healthy volunteers without history of CTS. Internal wrists dimensions, the presence of flexor muscle bellies in the carpal tunnel, and cross-sectional area of the median nerve were analyzed. The findings were correlated to gender, age, and BMI. Results. US demonstrated a square internal carpal tunnel configuration in CTS patients compared to controls (P<0.001). Patients with CTS showed a trend towards the presence of flexor muscles bellies in the carpal tunnel (odds ratio 1.77, 95% CI 0.337–8.33). CTS was present in women with higher BMI (P=0.015). Conclusion. US allowed detection of specific anatomical features at wrist level in CTS patients. This observation may enable—following confirmation in larger prospective studies—risk evaluation for CTS development.